Meaning and Function of Bride Prices in the Marriage Customs of the Bugis Community in Masohi City Central Maluku Regency - Anike Jacomina. M. Manuputty; Nua Aini Nahumarury (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
Dowry is one of the element important in customs marriage Bugis society which still practiced until moment This includes the Bugis people who live in Masohi City, Central Maluku Regency. The tradition of dowry money No only functioning as condition marriage, but also contains meaning related social with mark culture, honor family and relationships social in community. Research This aim for analyze meaning social and function ofdowry money in customs marriage Bugis community in Masohi City, Central Maluku Regency. Study This use approach qualitative with method descriptive. Data obtained through observation, interview deep with figure customs, figures society, as well as couples who carry out marriage Bugis customs, and documentation. Data analysis was carried out through stages data reduction, data presentation, anddata extraction conclusion. Research result show that the dowry money own meaning social as symbol respect to women and their families, social status indicators, and form not quite enough responsibility and readiness man in build House stairs. In addition, the dowry functioning as means tighten connection family, caring dignity family, and as mechanism social in maintain values Bugis customs in the middle change social. However thus, in in practice found existence adjustment the value of the dowry isnfluenced by conditions economy, education, anddynamics social public local. Study This expected can give contribution academic in development study sociology and anthropology culture, in particular related practice customs marriage Bugis society, as well as become reference for community and stakeholders interest in understand and preserve values culture local in a way contextual.